The Crucial Significance of Cyber Threat Intelligence in Mitigating Cyber Attacks - Eltayeb, Omer Eltayeb Omer (Journal of Ecohumanism, 2024)
Cyber Threat Intelligence (CTI) has risen to prominence in the constantly evolving cybersecurity landscape, playing a pivotal role in the protection of digital systems. Through a thorough examination of intelligence's many aspects and origins, an understanding of this field emerges. Information sharing and analysis centres serve as beacons of collaboration, exemplifying the collective vigilance required to combat such evolving threats. As we know, a threat actor may launch an attack against the system and spread malware. The ultimate objective of this particular cyber security breach is to manipulate, alter, or switch delivery mechanisms. Therefore, CTI must be integrated into existing cybersecurity practices in order to detect and comprehend the intentions and motivations of threat actors against the backdrop of persistent cyber threats. As businesses navigate the complexities of the digital landscape, the prudence of adopting an integrated approach to threat intelligence becomes glaringly apparent. Thus, this in-depth analysis tries to provide a potent instrument for organisations devising robust, adaptable cybersecurity strategies and bolsters knowledge of the defences that protect digital assets from an ever-changing sea of cyber threats.